A Case of Crimean-Congo Hemorrhagic Fever and Evaluation of Cases Admitted For Tick Bite - Akarsu, Saadet; Erensoy, Ahmet; Tosun, Mehtap Durukan; Cakici, Oya; Yildirmaz, Serap (Aves Yayincilik, Ibrahim Kara, 2008)
Aim: Crimean-Congo Hemorrhagic Fever (CCHF), is a zoonosis characterized, viral hemorrhagic disease which has high mortality and included in viral hemorrhagic fever syndromes. Our country has a suitable geography for lives of ticks. Ticks have essential role at tranmission of disease. We want to share our experience of first evaluation, treatment, follow up and official procedures of tick bite patients. Material and Method: 84 cases which have tick bite history enrolled to the study prospectively. Sistematic procedure of Ministry of Health prepared for tick bite, used. First by suggestion of infectious diseases specialist of our university, serum samples taken from needed cases and ticks which were still on the body or bringed to us analyzed by microbiology specialist of our hospital and determined their features. PCR study of 3 serum samples taken, done at Refik Saydam Hifzisihha Center. Results: Of all cases only at 3 of them clinic and laboratory findings were suggestive of CCHF. From 3 serum samples sent to Ministry of Health, only at one CCHF agent detected by PCR study. All cases discharged with cure and hemorrhage not seen at any case. Conclusion: If humans avoid contact, transmission can be prevented. By the way, as possible, should stay away of areas that found ticks. In a case of tick bite, it's suggested to obey to algorithm and follow up patients closely.
Keywords: Tick; Crimean-Congo Hemorrhagic Fever